Analisis Tantangan Moderasi Beragama di Era Digital melalui Perspektif Teori Filter Bubble dan Echo Chamber - Hidayah, Alfi Rohmatul; Nur, Moh. Asaddin (Institut Teknologi Sepuluh Nopember, 2024)
The digital era has revolutionized social interactions, including discussions on religious issues, through digital platforms. However, platform algorithms often foster filter bubbles and echo chambers, limiting access to diverse information and intensifying social polarization. Filter bubbles expose users only to content aligning with their views, while echo chambers amplify these views without engaging alternative perspectives. These dynamics pose challenges to interfaith dialogue and threaten religious moderation in Indonesia, a nation characterized by its vast religious diversity. This article examines these challenges using the concepts of filter bubbles and echo chambers as analytical lenses, focusing on how algorithms exacerbate polarized religious understanding and hinder openness to differing views. To address these issues, a comprehensive approach involving society, government, and digital platforms is essential. Enhancing digital literacy within society can cultivate critical thinking and openness to diverse perspectives. The government must establish policies promoting interfaith dialogue and curbing divisive content. Simultaneously, digital platforms should design algorithms that prioritize inclusivity, introduce varied perspectives, and foster harmonious interactions. Collaboration among these stakeholders can create a digital environment that upholds religious moderation, supports unity in diversity, and mitigates the risks posed by algorithm-driven polarization.